(untitled) (Journal of the College of Basic Education, 2022)
Despite the recent adoption of the terminological concept of differentiated education in the field of teaching, differentiated education is not a new phenomenon in the field of education and education, as some writings were found among the ancient Egyptians and Greeks that call for attention to learning that meets the different needs of learners, and from this As a starting point, a new concept of teaching and learning has emerged, which is differentiated education. (Al-Hulaisi, 2012: 36), Al-Laqani and Al-Jamal (2003) defined it as a style that relies on diversity, where there are individual differences among the students of one class, which means that the teacher’s reliance on one method does not necessarily lead to everyone learning the same amount and type.